The Effect of Organizational Communication, Work Motivation and Work Environment on Employee Performance - Saputra, Ade; Oktaria, Eka Trvilta; Loliyana, Rina (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
Employee performance is a critical factor in sustaining competitiveness within the bakery industry, which is characterized by intense competition and high service demands. This study aims to examine the influence of organizational communication, work motivation, and work environment on employee performance at Clarion Bread and Cake. The research employs a quantitative associative approach, using primary data collected through structured questionnaires distributed to 75 employees. The data were analyzed using multiple linear regression analysis, supported by partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²). The results indicate that work motivation and work environment have a positive and significant partial effect on employee performance, while organizational communication does not show a significant partial influence. However, when tested simultaneously, organizational communication, work motivation, and work environment jointly have a significant effect on employee performance. The coefficient of determination reveals that these three variables explain 35.3% of the variation in employee performance, while the remaining 64.7% is influenced by other factors not included in this study. In conclusion, although organizational communication does not independently affect performance, the combined role of communication, motivation, and work environment serves as a significant predictor of employee performance. Work motivation and work environment emerge as the most dominant factors. This study contributes practical insights for management in prioritizing motivational strategies and improving the work environment to enhance employee productivity. The limitation of this study lies in the relatively modest explanatory power, suggesting the need to explore additional variables in future research.